Tanycythere New Genus and its Significance for Jurassic Ostracod Diversity. (May 2014) - Cabral, Maria Cristina; Lord, Alan; Boomer, Ian; Loureiro, Isabel; Malz, Heinz
Abstract : The new genus Tanycythere (Crustacea, Ostracoda) is described from the Jurassic (Hettangian–Bathonian) of western and central Europe based on T. caudata new species, T. praecaudata praecaudata new subspecies, T. praecaudata parallela new subspecies, T. duartei new species, T. posteroelongata new species, and T. wattonensis new species. Another new species, T. procera, is described from the Lower Cretaceous (?Barremian). Recognition of a new genus comprising six new species and subspecies indicates that overall Jurassic and Early Cretaceous ostracod biodiversity is underestimated.